2015
DOI: 10.1086/682277
|View full text |Cite
|
Sign up to set email alerts
|

Offspring Provisioning Explains Clone-Specific Maternal Age Effects on Life History and Life Span in the Water Flea,Daphnia pulex

Abstract: Genetic inheritance underpins evolutionary theories of aging, but the role that nongenetic inheritance plays is unclear. Parental age reduces the life span of offspring in a diverse array of taxa but has not been explained from an evolutionary perspective. We quantified the effect that maternal age had on the growth and maturation decisions, life history, rates of senescence, and life span of offspring from three Daphnia pulex clones collected from different populations. We then used those data to test general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 92 publications
3
84
5
Order By: Relevance
“…To create different maternal age x diet treatments (i.e., HP‐Young, HP‐Old, LP‐Young, LP‐Old), we took a single neonate from the second clutch or the sixth clutch of four randomly chosen mothers from each diet treatment (Figure ). Previous studies have documented age effects from neonates selected as close as three clutches apart (Coakley et al, ; Plaistow et al, ). Thus, the selection of neonates from clutches two and six in our study is sufficient to induce age effects.…”
Section: Methodsmentioning
confidence: 99%
“…To create different maternal age x diet treatments (i.e., HP‐Young, HP‐Old, LP‐Young, LP‐Old), we took a single neonate from the second clutch or the sixth clutch of four randomly chosen mothers from each diet treatment (Figure ). Previous studies have documented age effects from neonates selected as close as three clutches apart (Coakley et al, ; Plaistow et al, ). Thus, the selection of neonates from clutches two and six in our study is sufficient to induce age effects.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a recent study demonstrated that non‐genetic maternal effects on growth and maturation consequently modulated the patterns of senescence and mortality in Daphnia pulex (Plaistow et al . ). So can environmental conditions shape senescence schedules?…”
Section: Introductionmentioning
confidence: 97%
“…The crustacean Daphnia magna exhibits clear maternal effects on size at birth and later performance traits (Ebert, ; Garbutt & Little, ; Lampert, ; Stjernman & Little, ; Tollrian, ): offspring of older mothers or those from calorie‐restricted mothers are larger and show enhanced resistance to pathogens than offspring of young or well‐fed mothers (Clark, Garbutt, McNally, & Little, ; Garbutt & Little, ). Almost half of offspring phenotypic variation (48%) in Daphnia pulex is due to maternal age (Plaistow, Shirley, Collin, Cornell, & Harney, ). Similar effects are observed in a variety of organisms.…”
Section: Introductionmentioning
confidence: 99%